Peranan peningkatan kompetensi SDM koperasi dalam Leverage kinerja(studi kasus SKKNI bidang koperasi jasa keuangan) - Elam Sari (Sekolah Pascasarjana Perbanas Jakarta, 2018)
Role of Increasing Human Resources Cooperative Competence In leverage of Performance (Case Study SKKNI Field Cooperative Financial Services). This study aims to analyze the role of SKKNI-KJK in realizing Professional Financial Services Cooperative Manager and build the reputation of KJK and to know how the implementation of competence in improving performance. The analysis is done by comparing the real world with problematic situation with conceptual model that exists during the implementation of SKKNI-KJK with the period 2007 to 2017. The analysis used with the method of thinking all-round system using 7 (seven) stage activities are grouped into two domains, namely Real world domains and thinking realms. The results of this study indicate that SKKNI-KJK has a very important role in creating high quality and high-quality human resources for the assurance of the quality of human resources and KJK Institution itself so that the achievement of KJK working professionals and the increasing reputation of cooperatives, as well as competence strongly positively affect the performance.. However, SKKNI-KJK has not been able to exert a significant influence on the development of KJK's quality in making a real contribution to the national economy. In the research also showed that SKKNI-KJK competency certification implementation in KSP NASARI Jakarta gives positive value and has an important role in improving managerial performance of competence.